1990
DOI: 10.1007/bf01536741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antral mast cells in nonulcer dyspepsia

Abstract: Two hundred twenty-five patients with the symptoms of nonulcer dyspepsia underwent clinical and endoscopic evaluation including histologic assessment of endoscopic biopsies. Mast cells were counted after special staining with low pH Alcian blue. Of 225 patients, 31 (13%) were found to have 11 or greater mast cells per high-power field. Endoscopic and routine histologic findings were similar between the subset of 31 patients with 11 or more mast cells and the entire group of 225. The 31 patients with increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…In the current study, we defined abnormal antral mast cell density as [15 cells/hpf. While no generally accepted standard exists for defining increased mast cell density, we chose[15 cells/ hpf because this corresponded to the 95th percentile value in a previous study of 225 adult FD patients [29]. We defined an abnormal eosinophil density as [10/hpf [30,31].…”
Section: Inflammationmentioning
confidence: 99%
“…In the current study, we defined abnormal antral mast cell density as [15 cells/hpf. While no generally accepted standard exists for defining increased mast cell density, we chose[15 cells/ hpf because this corresponded to the 95th percentile value in a previous study of 225 adult FD patients [29]. We defined an abnormal eosinophil density as [10/hpf [30,31].…”
Section: Inflammationmentioning
confidence: 99%
“…Anecdotal reports suggest that histamine receptor antagonists [60] and the well-known anti-histaminic effects of tricyclic antidepressants [61,62] may participate in the symptomatic improvement in functional gut disorders. In a recent uncontrolled study, 70% of 47 patients with chronic intractable diarrhoea, almost half of whom had IBS-D, had increased mast cells.…”
Section: Other Compounds With Proven or Potential Anti-inflammatory Pmentioning
confidence: 99%
“…Mast cell degranulation has also been detected by electron microscopy in the gastric mucosa of patients with peptic ulcer [17]. Moreover, therapy with histamine H 1 antagonists reduces the symptoms of patients with non-ulcer dyspepsia with increased mast cell numbers in their gastric biopsy specimens [29]. It has been suggested that mast cell activation by H. pylori factors is an early event leading to the release of inflammatory mediators that induce endothelial cells adhesion [30] and mediate the extravasation of inflammatory phagocytic cells [31].…”
Section: Discussionmentioning
confidence: 99%